Prevalence and risk factors of postpartum depression, general depressive symptoms, anxiety and stress (PODSAS) among mothers during their 4-week postnatal follow-up in five public health clinics in Perak: A study protocol for a cross-sectional study - Boon How Chew; Subashini Ambigapathy; Saidatul Akmar Mohammad Redzuan; Priyasini Suntharalingam; Thenmoli Palaniyappan; Venotha Ganasan; Puteri Normalina Megat Abu Bakar; Paream Kaur; Lili Zuryani Marmuji; V Paranthaman (BMJ Open)
Introduction Postpartum depression, general depressive symptoms, anxiety and stress (PODSAS) are often overlooked, and may cause morbidity to new mothers, their babies and families. This study aims to determine the point prevalence of depression (post partum and general), anxiety and stress among mothers in five public health clinics in Perak at 4 weeks postdelivery and identify their associated risk factors. Findings from this study will be used to identify the needs for early screening and detection, encourage development of interventions to reduce its occurrence and support mothers with PODSAS.Methods and analysis This cross-sectional study will recruit 459 postpartum mothers during their 4-week postnatal follow-up in five selected public health clinics in Perak from September 2019 to May 2020. Participants will be mothers aged 18 years and above at 4 weeks postdelivery who are able to understand the English and Malay languages. Non-Malaysians and mothers with known diagnosis of psychotic disorders will be excluded from the study. Sociodemographic information and possible risk factors of the participants will be captured via a set of validated questionnaires, postpartum depression (PPD) will be measured using the Edinburgh Postpartum Depression Scale questionnaire and general depressive symptoms, anxiety and stress will be measured using the 21-item Depression, Anxiety and Stress Scale. Data analysis will be conducted using SPSS V.25.0 (IBM). Besides descriptive statistics, multivariable regression analyses will be done to identify possible risk factors and their independent associations with depression (PPD and general depressive symptoms, combined and separately), anxiety and stress.Ethics and dissemination The study protocol was reviewed and approved by the Medical Research Ethics Committee, Ministry of Health Malaysia on 7 August 2019. Results of this study will be reported and shared with the local health stakeholders and disseminated through conference proceedings and journal publications.Registration number This study is registered in the Malaysian National Medical Research Register with the ID: NMRR-19-868-47647